Numerical study on the evolution of methane explosion regions in the process of coal mine fire zone sealing. (1st April 2021) - Wang, Guo-Qin; Shi, Guo-Qing; Wang, Yan-Ming; Shen, Hao-Yang
Highlights: Influence of CO and CO2 in fire smoke on methane explosion limits has been discussed. Mathematical model of fire source development and gas distribution under the effect of fire zone sealing is established. An innovative and feasible dynamic sealing simulation method is proposed. The law of gas migration and distribution in the fire zone under the effect of fire zone sealing is obtained. The evolution law of methane explosion region after the beginning of fire zone sealing is obtained. Abstract: To explore the distribution rules of methane explosion regions after the beginning of coal mine fire zone sealing, this paper analyzes the change law of methane explosion limits under the influence of CO2 and CO by using a thermal balance methodology. The distribution rules of methane, smoke and oxygen in the fire zone are obtained for different fire source locations. On this basis, the temporal and spatial distributions of the methane explosion regions at the working face are determined. The modeling results show that during the sealing process, the methane explosion limits are greatly affected by fire smoke. In the early stage of sealing, the methane explosion limit range in the fire zone is reduced due to the dilution of CO2, but later, due to the production of CO, the risk of methane explosion increases. A methane explosion region will appear in the working face tunnel within 1 h after the beginning of sealing, and the timing is closely related to the location of the fire source. When the fire source is located on the intake side of the working face, the methane explosion region first appears on the return side and has the longest duration among all the cases studied; the methane explosion region appears the earliest when the fire source is located on the return side of the working face, and the possibility of methane explosion is the largest in this case.